Fat properties and antinutrient content of rambutan (Nephelium lappaceum L.) seed during solid-state fermentation of rambutan fruit - Chai, Kong Fei; Mohd Adzahan, Noranizan; Karim, Roselina; Rukayadi, Yaya; M. Ghazali, Hasanah (Elsevier BV, 2019)
Rambutan seed is usually discarded during fruit processing. However, the seed contains a considerable amount of crude fat. Hence, the objective of this study was to investigate the fat properties and antinutrient content of the seed during fermentation of rambutan fruit. Results showed that the crude fat content of the seed reduced by 22% while its free fatty acid content increased by 4.3 folds after 10 days of fermentation. Arachidic acid was selectively reduced and was replaced by linoleic acid from the seventh day of fermentation onwards. Only 14.5% of triacylglycerol remained in the seed fat at the end of fermentation. The complete melting temperature, crystallization onset temperature and solid fat index at 37 °C of the fermented seed fat were higher than that of non-fermented seed fat. The saponin and tannin contents of the seed were reduced by 67% and 47%, respectively, after fermentation.